Enhanced electronic properties in mesoporous TiO2 via lithium doping for high-efficiency perovskite solar cells - Fabrizio Giordano (Nature Portfolio, 2016)
Perovskite solar cells are still plagued by hysteresis, despite the good charge transport properties of the perovskite counterpart. Here, the authors dope the mesoporous TiO2scaffold with lithium to improve the transport properties of this other important component of solar cells, and reduce the hysteresis.